PENERAPAN STRATEGI THINK TALK WRITE (TTW) DALAM PEMBELAJARAN KOOPERATIF UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA KELAS VII.1 SMPN 10 MANDAU - Sandra Vanessa; Titi Solfitri; Putri Yuanita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aims to improve the learning process and increase the student’s mathematics learning outcomes through the implementation of the Think-Talk-Write Strategy in Cooperative Learning. This type of research is the Classroom Action Research two cycle. The research was conducted in class VII1 SMPN 10 Mandau in the second semester of the 2016/2017 academic year with the subject of as many as 32 students, consist of 16 boys and 16 girls. The research instrument consists of learning devices and instrument data collectors. Learning device used in this research is the Syllabus, Lesson Plan and Worksheet. The instrument data collector used in this research is the observation sheet and math achievement test. Based on the data analysis of student learning outcomes, there is an increase in student learning outcomes in each cycle. Based on the result of the research showed that implementation of learning process on cycle II had happened improvement from implementation on cycle I. Weakness on cycle I is improved on implementation cycle II according with planning of improvement after reflection cycle I. Number of students that reach Minimum Mastery Criteria increase from basic score to daily test II. The number of students who reach Minimum Mastery Criteria on basic scor 12 person (37,5%), UH I amounted to 18 person people with percentage (56,25%) and UH II amounted to 22 person people with percentage (68,75%). Results of this research indicates that application of the Think-Talk-Write Strategy in Cooperative Learning can improve learning process and increase mathematics learning outcomes from the students at class VII1 SMPN 10 Mandau in the second semester academic years 2016/2017 .Keywords: Cooperative Learning, Think-Talk-Write Strategy, Learning Process, student’s mathematics learning outcomes, Classroom Action Research.